Teacher education in the context of cyberculture - Sousa, Francisco; Berbat, Marcio da Costa; Barros, Victor F. A. (Cadernos de Educação Tecnologia e Sociedade, 2018)
This special issue of BRAJETS â€“ Brazilian Journal of Education, Technology and Society â€“ is focused on the topic â€œTeacher education in the context of cybercultureâ€. The articles were written by researchers who have faced the challenge of reflecting on education and technology in various settings of teacher education. Such reflection has taken a variety of social perceptions on knowledge construction into consideration. As many procedures become automatic and connections between people become widespread, BRAJETS, through the publication of this special issue, addresses a contemporary issue: the potential of cyberculture for tranforming education and teacher edcuation. In order to assure quality and representativeness of the articles published in this journal, we subject them to a double-blind review. The reviewers are highly experienced researchers who have been extremely active in their fields of expertise. This special issue includes six texts whose authors disscuss teacher education in the context of cyberculture, through various approaches and interpretations, considering the diversity of contexts that have been studied. The findings from the studies presented in this issue might help readers become more familiar with different ways of using ICT in educational networks. Achievements and obstacles are identified and discussed under the assumption that educational change prompted by cyberculture seems inevitable, even if it does not break continuity with the past. We hope readers enjoy this issue of BRAJETS and use it as a source of new ideas for research and practice